MODEL PENGADAAN LAHAN UNTUK RUANG TERBUKA HIJAU (RTH) KOTA SIGLI - Muhammad Khaled; Muhammad Isya; Ashfa Achmad (Prodi Magister Teknik Sipil Unsyiah, 2021)
Green Open Space (RTH) in urban areas has value for the needs and needs of parks and recreation. The allocation of twenty percent of public green open space from the urban area of Sigli City as stipulated in the Pidie Regency Qanun Number 5 of 2014 concerning the Pidie Regency Spatial Plan for 2014-2034 has not yet been achieved. This study aims to examine the factors that influence land acquisition and how land acquisition models are appropriate for public green space in the city of Sigli. This research uses quantitative methods. The data obtained in the form of ordinal data and nominal dichotomos. The data was analyzed by logistic regression methods and Focused Group Discussion (FGD). The model of the logistic regression equation formed is: